Efektivitas Penerapan Metode Iqro’ untuk Meningkatkan Kemampuan Membaca Al-Qur’an Anak Usia Dini di TK Mentari Batu Nampar: The Effectiveness of Applying the Iqro' Method to Improve the Al-Qur'an Reading Skills of Early Childhood Children at Mentari Kindergarten - Muhamad Zaril Gapari (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
In this era of globalization, many Muslims still cannot read the Quran. This is due to unfavorable circumstances and the inability of those studying the Quran to choose an effective reading method. The objectives to be achieved in this study are To find out how the implementation process and what are the challenges with the Iqro' method in improving the ability to read the Qur'an of early childhood in Mentari Kindergarten. The research method used is descriptive qualitative with a survey research design. In this study, researchers used three data collection techniques, namely observation, interviews and documentation. The data analysis technique that has been used is descriptive analysis technique with components of data reduction, data presentation, and verification. The results of the study, it can be concluded that 1) The process of implementing the Iqro' method involves the stages of selection, identification of abilities, explanation of materials, talaqqi sessions, interaction, and reinforcement inside and outside the classroom; 2) The application of the Iqro' method has a significant positive impact in improving the ability to read the Qur'an of early childhood in Mentari Batu Nampar. This method not only improves reading skills and tajwid understanding, but also motivates students to be more active and enthusiastic in studying the Qur'an. These impacts create a learning environment that supports the spiritual and academic development of children; and 3) The application of the Iqro' method in improving the ability to read the Qur'an of early childhood children at Mentari Batu Nampar Kindergarten faces a number of challenges, namely difficulties in understanding tajwid, lack of family support, limited time, and the need for variation in learning.